Contrasting genomic profiles from metastatic sites, primary tumors, and liquid biopsies of advanced prostate cancer. Issue 24 (11th August 2021) - Necchi, Andrea; Cucchiara, Vito; Grivas, Petros; Bratslavsky, Gennady; Jacob, Joseph; Spiess, Philippe E.; Sokol, Ethan S.; Killian, Jonathan Keith; Lin, Douglas; Ramkissoon, Shakti; Huang, Richard S. P.; Madison, Russell W.; et al.
Abstract : Background: This study assessed the contrasting genomic profiles from the primary tumors (PTs), metastatic (MET) sites, and circulating tumor DNA (ctDNA) of patients with prostate cancer (PC). Methods: A total of 1294 PC tissue specimens and 2462 ctDNA specimens underwent hybrid capture–based comprehensive genomic profiling (CGP). Specimens included tissue from PTs; MET biopsies from bone, liver (LIV), lung (LU), brain (BN), lymph node, and soft tissue sites; and ctDNA. Results: Differences in alteration frequencies between PT, MET, and ctDNA specimens for selected genes were observed. TMPRSS2:ERG fusion frequencies were similar between PTs and MET sites (35% vs 33%) but varied among MET sites. Genomic alterations (GAs) in AR were lowest in PTs (2%) and highest in MET sites (from 24% in LU to 50% in LIV). BN had the highest genomic alterations/tumor (8) and enrichment for PTEN GAs. The BRCA2 GA frequency varied from 0% in BN to 15% in LIV. ERBB2 amplification was increased in MET sites in comparison with PTs. RB1 GAs were increased in LIV. Biomarkers potentially associated with an anti‐PD(L)1 response included CDK12 GAs (16% in LU) and a microsatellite instability–high status (29% in BN). Analyses of ctDNA featured a broad spectrum of GAs similar to those detected across MET sites. Conclusions: CGP of PTs, MET sites, and ctDNA in PC exhibited differences most likely associated with tumor progression, clonal evolution, and exposure to systemic therapies; ctDNA can also capture a broad range of potential therapeutic opportunities for patients with PC. Abstract : Tumor tissue genomic alterations from primary prostate tumors and metastatic sites show significant heterogeneity, and this suggests possible tumor evolution, natural selection, and/or tumor adaptation. Circulating tumor DNA testing can be a noninvasive, potentially serial assay that may provide a real‐time representation of the evolutionary cancer state throughout therapy.